Game time - Murphy, Stuart J., 1942-; Jabar, Cynthia (New York : HarperCollinsPublishers, 2000)
Calendars and clocks keep track of passing time as the Huskies prepare for and compete in the championship soccer game against the Falcons.
"Level 3, ages 7 up"--P. [4] of cover.
390
Keywords: Soccer -- Fiction; Time -- Fiction; Clocks and watches -- Fiction; Time -- Juvenile literature; Clocks and watches -- Juvenile literature